New 1, 2, 4-oxadiazole derivatives with positive mGlu4 receptor modulation activity and antipsychotic-like properties. (1st January 2022) - Stankiewicz, Anna; Kaczorowska, Katarzyna; Bugno, Ryszard; Kozioł, Aneta; Paluchowska, Maria H.; Burnat, Grzegorz; Chruścicka, Barbara; Chorobik, Paulina; Brański, Piotr; Wierońska, Joanna M.; Duszyńska, Beata; Pilc, Andrzej; et al.
Abstract: Considering the allosteric regulation of mGlu receptors for potential therapeutic applications, we developed a group of 1, 2, 4-oxadiazole derivatives that displayed mGlu4 receptor positive allosteric modulatory activity (EC50 = 282–656 nM). Selectivity screening revealed that they were devoid of activity at mGlu1, mGlu2 and mGlu5 receptors, but modulated mGlu7 and mGlu8 receptors, thus were classified as group III-preferring mGlu receptor agents. None of the compounds was active towards hERG channels or in the mini-AMES test. The most potent in vitro mGlu4 PAM derivative 52 (N-(3-chloro-4-(5-(2-chlorophenyl)-1, 2, 4-oxadiazol-3-yl)phenyl)picolinamide) was readily absorbed after i.p. administration (male Albino Swiss mice) and reached a maximum brain concentration of 949.76 ng/mL. Five modulators (34, 37, 52, 60 and 62 ) demonstrated significant anxiolytic- and antipsychotic-like properties in the SIH and DOI-induced head twitch test, respectively. Promising data were obtained, especially for N-(4-(5-(2-chlorophenyl)-1, 2, 4-oxadiazol-3-yl)-3-methylphenyl)picolinamide (62 ), whose effects in the DOI-induced head twitch test were comparable to those of clozapine and better than those reported for the selective mGlu4 PAM ADX88178. Graphical Abstract: UF0001